2021
DOI: 10.1111/joca.12393
|View full text |Cite
|
Sign up to set email alerts
|

A model of consumer life‐satisfaction amidst the COVID‐19 pandemic: Evidence and policy implications

Abstract: The COVID‐19 pandemic has dramatically impacted the lives of consumers across the globe. What guidance can consumer researchers and policymakers provide consumers to elicit adaptive responses that contribute to their life‐satisfaction under these adverse conditions? To this end, we develop and test an adaptive response model and demonstrate its impact on the life‐satisfaction of the consumers experiencing the pandemic in Turkey. Our model suggests that amidst COVID‐19, seeking emotional help triggers the posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 88 publications
0
15
0
1
Order By: Relevance
“…This research contributes to theory in three ways. First, through empirically identifying and validating distinctive segments of consumers based on their cognitive, affective, and behavioral responses to the COVID‐19 pandemic, we add to the nascent but growing literature aimed at understanding the impact of the pandemic on consumers (e.g., Cronshaw, 2021; Ekici & Watson, 2021; Jin & Ryu, 2021; Nayal et al, 2021). Second, in using segmentation variables theoretically grounded in the Extended Parallel Process Model (Witte, 1992; Witte et al, 1996) and the Theory of Reasoned Action (Fishbein & Ajzen, 1975), this research illustrates the predictive power of the EPPM and the TRA and extends both theories to the novel and evolving context of the COVID‐19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This research contributes to theory in three ways. First, through empirically identifying and validating distinctive segments of consumers based on their cognitive, affective, and behavioral responses to the COVID‐19 pandemic, we add to the nascent but growing literature aimed at understanding the impact of the pandemic on consumers (e.g., Cronshaw, 2021; Ekici & Watson, 2021; Jin & Ryu, 2021; Nayal et al, 2021). Second, in using segmentation variables theoretically grounded in the Extended Parallel Process Model (Witte, 1992; Witte et al, 1996) and the Theory of Reasoned Action (Fishbein & Ajzen, 1975), this research illustrates the predictive power of the EPPM and the TRA and extends both theories to the novel and evolving context of the COVID‐19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…While some initial investigations have linked perceptions of the pandemic to individual differences such as personality dimensions (Aschwanden et al, 2021) and tracked the process that consumers have followed in response to the pandemic (Kirk & Rifkin, 2020), others have shown that consumer perceptions of risk affect downstream shopping preferences, such as home delivery vs. in‐store shopping (Grashuis et al, 2020). More recent research has started to examine the impact of the pandemic on outcome variables beyond purchase behaviors such as life satisfaction (Ekici & Watson, 2021), prosocial giving, and charitable donations (Jin & Ryu, 2021). However, the variation in consumer reactions has made it difficult for marketers to understand different consumer segments based on perceptions of and responses to the pandemic and what proportion of each segment exists in the overall marketplace.…”
Section: Introductionmentioning
confidence: 99%
“…Postavila sem tudi hipotezo o pomenu družbenega vpliva. Covid-19 je na državljane vplival na veliko načinov (Anglim & Horwood, 2021;Ekici & Watson, 2022), zato je tudi pričakovati veliko govora o aplikaciji za zajezitev širjenja bolezni. Ker covid-19 povzroča skrbi zaradi ogroženost osebnega zdravja, se veliko posameznikov naslanja na mnenja njim pomembnih ljudi (Zhao in drugi, 2018).…”
Section: Napovedovalci Utautunclassified
“…Therefore, it seems that reflections of COVID-19 on how consumers behave have taken the attention of scholars. Herein, topics such as consumer behavior in retail sector (Pantano, et al, 2020), consumer well-being and consumption habits, (Nayal, et al, 2021), consumer life satisfaction and escape behavior (Ekici and Watson, 2021), attitudes toward singleuse plastic food packaging (Kitz, et al, 2021), consumer ethical decision making (He and Harris, 2020), consumption practices (Gordon-Wilson, 2021), prosocial consumption (da Silva Terres, et al, 2020), impulse buying behavior (Ahmed, et al, 2020), reacting, coping and adapting behaviors (Kirk and Rifkin, 2020), panic buying (Chakraborti and Roberts, 2021), consumer mindset and their preferences (Septianto and Chiew, 2021), behavioral processes of purchase satisfaction and repurchase (Kursan Milaković, 2021), omni channel, retailing and purchase behavior (Verhoef, 2021), emotions and shopping behavior (Szymkowiak, et al, 2021), purchasing (Mehrolia, et al, 2021;Kursan Milaković, 2021) and compensatory consumption (Ulqinaku, et al, 2020) were studied. When considering that marketing strategies should be shaped according to consumers' behaviors and COVID-19 has dramatically changed the behaviors of people, the intense efforts to comprehend consumers' behaviors in the COVID-19 is understandable.…”
Section: Marketingmentioning
confidence: 99%